ECOLOGICAL ASPECTS OF WASTE MANAGEMENT INTERREGIONAL COOPERATION (ON THE EXAMPLE OF THE PROGRAM OF POLLUTED LANDS’ REHABILITATION) - Pysarenko, P. V.; Taranenko, A. O.; Chalcev, D. V.; Kahykalo, O. O.; Gryshyna, K. E.; Korchagin, O. P. (Scientific Progress & Innovations, 2020)
One of the most important tasks of organizing interregional cooperation in the field of waste management is reducing the area of polluted lands, the formation of which is due to the functioning of this field. Current-ly, in connection with the development of market relations, the issues related to the formation of land market are of particular significance. Therefore, today it is important to identify factors, their relationships and de-pendencies, which have a significant impact on cost characteristics of land resources in districts or their considerable parts. The level of ecological danger of dumping ground was carried out by the authors using ecological-audit assessment. The calculation of scattering harmful substances was carried out according to OND-86 technique on the basis of EOL 2000 software. The authors developed methodological approaches to creating a rehabilitation program for polluted lands with solid wastes. The implementation of this program will not only return the natural and anthropogenic environment to the state which suits natural and social situation of the studied area, but also significantly improve cost and other economic indicators of lands in the whole district. Factors of ensuring the quality of city and suburban area life, minimizing the cost for mu-nicipal waste disposal, taking into account the environmental factor were determined Optimization of these factors was conducted on the example of Poltava city and suburban areas. The conducted calculations of costs minimization of solid waste dumping ground arrangement taking into account the minimization of eco-logical risk to the environment, allowed establishing the permissible load of municipal waste amount on suburban area, considering the equality of conditions for the population. The necessity of introducing com-plex (territorial) rates of production and consumption waste formation and limits on their location on the territory was proved. The expediency of specialized fund creation ensuring rational resource application by resource users for direct performance of a complex of rehabilitation measures was also considered.